Diversity and distribution patterns of Ecuador’s dung beetles (Coleoptera: Scarabaeinae) - Villamarin-Cortez, Santiago; Hankin, Lacey; Coronado, Stephanie; Macdonald, Jacob; Noriega, Jorge Ari (Frontiers in Ecology and Evolution, 2022)
Ecuador harbors an astounding number of ecosystems and species. However, anthropogenic land-use changes are the primary drivers of biodiversity loss in major taxonomic groups, especially insects. Among them, the Scarabaeinae subfamily containing dung beetles, is an excellent taxon for studying taxonomic and functional diversity, as they are relatively stable taxonomically and have a wide variety of ecological services. Their distribution is mainly influenced by biogeography and climate as their main ecological and environmental factors will allow us to quantify what aspects of diversity are being impacted under different circumstances and at different scales. To understand the main drivers of dung beetle’s distribution, we conduct an analysis utilizing a museum database from the National Institute of Biodiversity, Ecuador (INABIO) of over 5000 dung beetle specimens collected throughout the country, addressing the following questions: i) How does tribe distribution vary across climatic and elevational gradients? and ii) How does functional and taxonomic beta diversity vary across spatial scales? To address these questions, we focused on three main tribes: Canthonini, Coprini, and Phanaeini. performing generalized linear models to estimate Ecuador’s distributions based on climate to explore potential predictor variables, along with taxonomic and functional beta diversity across scales. Elevation, precipitation, and temperature were the main variables influencing dung beetle distribution. The Phanaeini distribution model is significantly better at predicting dung beetle presence throughout Ecuador than Canthonini and Coprini. Functional diversity showed much larger turnover rates than taxonomic diversity, primarily due to high turnover in functional groups at larger scales, suggesting that dung beetles show high levels of habitat specialization. Resulting in taxonomic and functional beta diversity being higher in Amazonia than the Coast. Our findings suggest that dung beetles are not found in areas above 2000m, mainly because dung beetles are well adapted to warmer and moist climatic regions. Precipitation and elevation are consistently essential variables for predicting Canthonini and Coprini presence, while temperature explains Phanaeini presence. Low levels of species turnover at the regional scale may be because the total species richness in Ecuador is different, resulting in higher taxonomic and functional beta diversity in the Amazon than in the Coast.